2020
DOI: 10.1016/j.jiph.2020.06.015
|View full text |Cite
|
Sign up to set email alerts
|

An analytical study on the awareness, attitude and practice during the COVID-19 pandemic in Riyadh, Saudi Arabia

Abstract: Background Coronavirus disease (COVID-19) is an infectious disease caused by a new variable of the Coronaviridae family. COVID-19 spreads primarily by contacting the virus either from a COVID-19-infected individual through coughing or sneezing or from COVID-19-contaminated surfaces. On March 12, 2020, the World Health Organization (WHO) announced COVID-19 as a pandemic. The government of Saudi Arabia was among the first countries in the world to take quick and serious pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
146
12
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(247 citation statements)
references
References 31 publications
49
146
12
13
Order By: Relevance
“…The present study showed that in response to COVID-19, men were less likely to take protective behavior than women. This coincides with the research in Saudi Arabia and Pakistan [ 27 , 28 ]. Studies suggest that targeted health education should be conducted for this high-risk population that is particularly vulnerable to COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that in response to COVID-19, men were less likely to take protective behavior than women. This coincides with the research in Saudi Arabia and Pakistan [ 27 , 28 ]. Studies suggest that targeted health education should be conducted for this high-risk population that is particularly vulnerable to COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…These findings were consistent with the earlier published data on COVID-19 [13][14][15][16][17][18][19] in Saudi Arabia. The earlier publications [13][14][15][16][17][18][19] have mentioned the leading indicators of COVID-19 (fever, shortness of breath, cough, etc. ); its incubation period (2-14 days); the risk of COVID-19 in patients with associated diseases (hypertension, diabetes, and cancer, etc.…”
Section: Resultssupporting
confidence: 93%
“…These articles have also stated that presently, there no active cure for COVID-19. The data of Table 2 and Table 3 is also in concurrence with the earlier studies [13][14][15][16][17][18][19], which discuss the initiation, spread, symptoms, & complications of COVID-19 in different populations. They also highlight the preventive measures to be followed, government strategic plans, and the importance of public education about the COVID-19.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations